2017
DOI: 10.1103/physreve.96.063113
|View full text |Cite
|
Sign up to set email alerts
|

Boundary conditions for a one-sided numerical model of evaporative instabilities in sessile drops of ethanol on heated substrates

Abstract: The work is focused on obtaining boundary conditions for a one-sided numerical model of thermoconvective instabilities in evaporating pinned sessile droplets of ethanol on heated substrates. In the one-sided model, appropriate boundary conditions for heat and mass transfer equations are required at the droplet surface. Such boundary conditions are obtained in the present work based on a derived semiempirical theoretical formula for the total droplet's evaporation rate, and on a two-parametric nonisothermal app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Semenov et. al derive in [26] and employ in [25] analytical equations for the unsteady diffusionlimited evaporation from sessile droplets, which agree with the numerical results of [28]. However, these unsteady effects are small on time scales larger than the time required for the Brownian particle to pass the characteristic length R.…”
Section: A Diffusion Of Vapor In Airsupporting
confidence: 73%
See 1 more Smart Citation
“…Semenov et. al derive in [26] and employ in [25] analytical equations for the unsteady diffusionlimited evaporation from sessile droplets, which agree with the numerical results of [28]. However, these unsteady effects are small on time scales larger than the time required for the Brownian particle to pass the characteristic length R.…”
Section: A Diffusion Of Vapor In Airsupporting
confidence: 73%
“…The authors have observed Marangoni instability in an ethanol droplet of capillary size on a heated and highly conductive substrate. They also performed numerical simulations by one-sided model described in [26], where they took into account, in particular, an unsteady diffusion-limited evaporation for non-isothermal pinned sessile droplet and the Stefan flow in the gas. After solving the heat transfer equation in the droplet bulk and carrying out the numerical simulation, the results obtained have agreed well with the experiment for the contact angle θ ≈ 29.3 • .…”
Section: Introductionmentioning
confidence: 99%
“…In order to further refine the suggested model, one has to consider J, which depends on time t, as well. For example, dependencies J(r, t) are suggested in [63][64][65][66].…”
Section: Advectionmentioning
confidence: 99%
“…( 11) with the three boundary conditions Eqs. ( 10) - (12) , we obtain the temperature distribution inside the water layer as:…”
Section: Average Temperature Of Droplet Base Surfacementioning
confidence: 99%